2012
DOI: 10.1177/1470320312452027
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of AGT and NOS3 gene polymorphisms with conventional risk factors increases predisposition to hypertension

Abstract: Renin-angiotensin and kallikrein-kinin systems are interconnected, regulating blood pressure homeostasis. We have demonstrated the interactions among polymorphisms of the angiotensinogen (AGT) and endothelial nitric oxide synthase (NOS3) genes and conventional risk factors affecting the hypertension occurrence. Individuals were recruited (n=192) and classified into hypertensive (HG; n=140) and normotensive (NG; n=52) groups. The genotypic distribution of the Met235Thr (AGT) and Glu298Asp (NOS3) polymorphisms d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…The pathogenesis of hypertension involves major and minor genes and ambient influences, [22,23] in which the gene-gene and gene-environment interaction exist. [24][25][26] In this study, we did not observe the genetic variant, rs275653, in AGTR1 promoter region that was associated with hypertension. It suggested that AGTR1 rs275653 locus polymorphism may not be a valuable genetic marker for differential risk of essential hypertension among Chinese farmers.…”
Section: Discussioncontrasting
confidence: 65%
“…The pathogenesis of hypertension involves major and minor genes and ambient influences, [22,23] in which the gene-gene and gene-environment interaction exist. [24][25][26] In this study, we did not observe the genetic variant, rs275653, in AGTR1 promoter region that was associated with hypertension. It suggested that AGTR1 rs275653 locus polymorphism may not be a valuable genetic marker for differential risk of essential hypertension among Chinese farmers.…”
Section: Discussioncontrasting
confidence: 65%
“…Several genetic profiles have been identified as factors that influence the blood pressure homeostasis, such as endothelial nitric oxide synthase (eNOS), or polymorphisms encountered in the human angiotensinogen gene (AGT). 12,13…”
Section: Definitionsmentioning
confidence: 99%
“…Diets high in NaCl increase the preponderance of hypertension in the population [42]. Genetic altercations in the renin-angiotensin system are linked to increased hypertension [43]. Age itself escalates blood pressure for the majority of individuals [44].…”
Section: Improving Animal Models: Role Of Comorbidities and Lifestylementioning
confidence: 99%